P24 Caffeine in preterm neonates: impact on sleep wake regulation. Issue 6 (17th May 2019) - Datta, AN; Koch, G; Schönfeld, N; Jost, K; Atkinson, A; Schulzke, SM; Pfister, M
Abstract : Background: Sleep wake regulation undergoes distinctive maturational changes. Ultradian sleep wake rhythm predominates at preterm age and is mainly driven by the internal clock. Increased perinatal morbidity in preterm neonates often appears with breathing disorders, among which apnea of prematurity (AOP) is the most frequently observed. Pharmacological support with caffeine has been successfully employed in the treatment of AOP. Nowadays, caffeine citrate is administered to all preterm neonates suffering from AOP. Objective of our study was a quantitative investigation of whether caffeine citrate treatment for reduction of apnea and bradycardia of prematurity affects sleep-wake behavior in preterm neonates. Methods: Observational study of 64 preterm neonates during their first five days of life with gestational age (GA) < 32 weeks or very low birth weight of < 1500 g. Total of 52 patients treated with caffeine and 12 controls without caffeine were included. Sleep-wake behavior was scored in wakefulness (W), active sleep (AS), and quiet sleep (QS) associated with physical and cerebral regeneration. Individual caffeine concentration of every neonate was simulated with a pharmacokinetic model. Results: For increasing caffeine concentration, W increased, AS decreased, and QS was unchanged for GA > or = 28 weeks. No caffeine effect for GA < 28 weeks could be demonstrated. Maturational effects could be seen when comparing preterm neonates of GA >32 weeks with a birth weight of < 1500 g with very preterm neonates born of GA < 32: Neonates born >32 weeks had a significantly higher amount of W and lower percentage of AS. Conclusions: Treatment of apnea and bradycardia as well as stabilization of respiration with standard caffeine treatment is not at cost of QS, i.e. time for physical and cerebral regeneration during sleep remains unchanged. There is an increased fraction of W, alertness and most probably also arousability. Disclosure(s): Nothing to disclose